Corin Mutations K317E and S472G from Preeclamptic Patients Alert Zymogen Activation and Cell Surface Targeting - Dong, Ningzheng (American Society for Biochemistry and Molecular Biology, 2014)
Corin is a membrane-bound serine protease that acts as the atrial natriuretic peptide (ANP) convertase in the heart. Recent studies show that corin also activates ANP in the pregnant uterus to promote spiral artery remodeling and prevent pregnancy-induced hypertension. Two CORIN gene mutations, K317E and S472G, were identified in preeclamptic patients and shown to have reduced activity in vitro. In this study, we carried out molecular modeling and biochemical experiments to understand how these mutations impair corin function. By molecular modeling, the mutation K317E was predicted to alter corin LDL receptor-2 module conformation. Western blot analysis of K317E mutant in HEK293 cells showed that the mutation did not block corin expression on the cell surface but inhibited corin zymogen activation. In contrast, the mutation S472G was predicted to abolish a β-sheet critical for corin frizzled-2 module structure. In Western blot analysis and flow cytometry, S472G mutant was not detected on the cell surface in transfected HEK293 cells. By immunostaining, the S472G mutant was found in the ER, indicating that the mutation S472G disrupted the β-sheet, causing corin misfolding and ER retention. Thus, these results show that mutations in the CORIN gene may impair corin function by entirely different mechanisms. Together, our data provide important insights into the molecular basis underlying corin mutations that may contribute to preeclampsia in patients.